The Temporal and Spatial Bias of Information Flow on New Media Platforms during Covid-19 Pandemic - et. al., Fei Tong , (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Since December 2019, a new infectious disease, " corona virus disease " (COVID-19), mainly lung lesion, has been emerging in China. The outbreak of covid-19 coincided with the Chinese New Year in 2020. The rapid spread of the disease triggered public panic and an overwhelming number of news reports on new media platforms. However, information does not always equate with the way of communication. The communication bias happened in the flow of information. This paper takes the information flow about covid-19 before 26th December, 2020 as a model, and compares the time of information flow in the early development of the epidemic with the approach of Edmund Carpenter’s "explorations in media and anthropology" and Harold A. Innis’ "the bias of communication ". The bias of time and of information delivered during the pandemic is examined. The study further focuses on the reflection and response of Chinese new media platforms and information platforms towards the public opinion management.